2022
DOI: 10.3847/1538-4357/ac3aeb
|View full text |Cite
|
Sign up to set email alerts
|

The Estimation of Fundamental Physics Parameters for Fermi-LAT Blazars

Abstract: Aiming to delineate the physical framework of blazars, we present an effective method to estimate four important parameters based on the idea proposed by Becker & Kafatos, including the upper limit of central black hole mass M, the Doppler factor δ, the distance along the axis to the site of the γ-ray production d (which then can be transformed into the location of γ-ray-emitting region R γ ) and the propagation angle with respect to the axis of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 147 publications
1
13
0
Order By: Relevance
“…It is that the changing-look blazars mostly lie above the dividing lines proposed by Ghisellini et al (2011) andSbarrato et al (2012). Pei et al (2022) studied the correlation L Disk /L Edd vs L γ /L Edd , assuming L Disk = 10L BLR , and it was clearly shown in Figure 5 of their work that the FSRQs and the changing-look blazars have larger accretion ratios than the BL Lac objects. They have proposed an "appareling zone," 2.0 × 10 −4 L BLR /L Edd 8.5 × 10 −3 , to select changing-look blazar candidates, and we found that there are 46 (taking 82.1%) changing-look blazars in our sample that lie in this zone.…”
Section: The Accretion Ratio Of Changing-look Blazarsmentioning
confidence: 95%
“…It is that the changing-look blazars mostly lie above the dividing lines proposed by Ghisellini et al (2011) andSbarrato et al (2012). Pei et al (2022) studied the correlation L Disk /L Edd vs L γ /L Edd , assuming L Disk = 10L BLR , and it was clearly shown in Figure 5 of their work that the FSRQs and the changing-look blazars have larger accretion ratios than the BL Lac objects. They have proposed an "appareling zone," 2.0 × 10 −4 L BLR /L Edd 8.5 × 10 −3 , to select changing-look blazar candidates, and we found that there are 46 (taking 82.1%) changing-look blazars in our sample that lie in this zone.…”
Section: The Accretion Ratio Of Changing-look Blazarsmentioning
confidence: 95%
“…It is that the 'Changing-look' blazars mostly lie above the dividing lines proposed by Ghisellini et al (2011) and Sbarrato et al (2012). Pei et al (2022) studied the correlation L Disk /L Edd vs L γ /L Edd , assuming L Disk = 10L BLR , and it was clearly shown in Figure 5 of their work that the FSRQs and the 'Changing-look' blazars have larger accretion ratio than the BL Lacs. They have proposed an 'appareling zone', 2.0 × 10 −4 ≤ L BLR /L Edd ≤ 8.5 × 10 −3 , to select 'Changing-look' blazars candidates, and we found that there are 46 (taking 82.1%) 'Changing-look' blazars in our sample that lie in this zone.…”
Section: The Accretion Ratio Of 'Changing-look' Blazarsmentioning
confidence: 93%
“…In this work, we have focused our research on the location of the blazar emission region. We applied a timescale of 1 day, which was suggested by Nalewajko (2013); as a typical variability timescale in the source frame in the Fermi γ-ray band, this timescale has been used in many works (e.g., Ghisellini et al 1998;Fan et al 2013;Nalewajko 2013;Chen 2018;Pei et al 2022). One can set an upper limit on the emission region size via inequality (6), thus its distance from the SMBH can be estimated via Equation ( 7).…”
Section: The Location Of the Emission Regionmentioning
confidence: 99%